Rutinitas Petani Arak Di Karangasem Bali Sebagai Ide Penciptaan Karya Seni Patung Naturalis - Suarsa, Si Ngurah; Mustika, I Ketut; Sukarya, I Wayan (Program Studi Seni Murni ISI Bali, 2024)
The routine of arak farmers in Karangasem Bali is very interesting to be made an object of research on the creation of fine art (statues) with the title